2018
DOI: 10.1007/978-3-319-98020-1_49
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Scalable Planar Scissor Linkages with Anti-parallelogram Loops

Abstract: Scissor linkages are commonly used as mechanisms for scaling objects. They constitute a significant portion of deployable structures. Since 1960s many researchers sought to form novel structures using the scissor units. In 1990s Hoberman brought a new perspective to the field when he used the loops, not the units to form linkages. Starting from mid 2000s, other researchers joined into this new approach of design. One of the latest researches presented a design for scaling a circular forms with antiparallelogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…[Hoberman et al, 2013] This way, he is able to form angulated units with constant subtended angles. 3) assemblies in various configurations [24][25][26]. These assemblies are special cases of one of the findings of this study and can be found under Section 5 -Linkage 4.…”
Section: Loop Assembly Methodsmentioning
confidence: 82%
“…[Hoberman et al, 2013] This way, he is able to form angulated units with constant subtended angles. 3) assemblies in various configurations [24][25][26]. These assemblies are special cases of one of the findings of this study and can be found under Section 5 -Linkage 4.…”
Section: Loop Assembly Methodsmentioning
confidence: 82%
“…Another study of the authors is by Gür et al [42] where they made the use of a loop that was not considered previously in scissor structures: the antiparallelogram. Also known as crossed-parallelogram or contra-parallelogram, it is a complex quadrilateral that intersects itself, though the intersection point does not provide a joint.…”
Section: Loop-based Methodsmentioning
confidence: 99%
“…Gür et al [43] also investigated structures approximating free-form curves. The curve is handled as the target form at fully deployed state and loops are scaled in between discrete nodes on the curve.…”
Section: Loop-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key issues of the design process for these structures is the dimensional synthesis of the mechanisms with articulated bars, so that the structures have the highest possible degree of deployability and, at the same time, occupy as little space as possible when folded [11], [12], [13]. In this paper, dimensional synthesis and simulation of some deployable mechanisms based on a modified scissor mechanism [ ] will be presented.…”
Section: Introductionmentioning
confidence: 99%